The legal protections of language in the Euopean Union - Lucheroni, Aislinn (Trinity College (Dublin, Ireland). School of Law, 2015)
This thesis investigates the legal protection of languages within the legal system of the European Union (EU). It aims to determine the nature and scope of this legal protection, taking an interdisciplinary approach. This interdisciplinary doctrinal research investigates the multilingual legal system of the EU.
Keywords: Law, Ph.D.; Ph.D. Trinity College Dublin.